2018
DOI: 10.1371/journal.pone.0194089
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic acetylcholine receptor (CHRN) expression and function in cultured human adult fungiform (HBO) taste cells

Abstract: In rodents, CHRNs are involved in bitter taste transduction of nicotine and ethanol. Currently, it is not clear if CHRNs are expressed in human taste cells and if they play a role in transducing the bitter taste of nicotine and ethanol or in the synthesis and release of neurohumoral peptides. Accordingly, we investigated the expression and functional role of CHRNs in HBO cells. Using molecular techniques, we demonstrate that a subset of HBO cells express CHRNs that also co-express TRPM5, T1R3 or T2R38. Exposin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 54 publications
(102 reference statements)
0
6
0
Order By: Relevance
“…3.3.4) ( 170 , 171 , 349 , 350 ). Again, using HBO cells, Ozdener and colleagues ( 351 ) showed that T2R-expressing cells express nicotinic receptors and respond directly to nicotine and acetylcholine, producing transient elevations in intracellular calcium. The significance of this opus is that it may provide a mechanism for the taste disturbances that are a side effect of certain anticholinergic drugs.…”
Section: Research In Progressmentioning
confidence: 99%
“…3.3.4) ( 170 , 171 , 349 , 350 ). Again, using HBO cells, Ozdener and colleagues ( 351 ) showed that T2R-expressing cells express nicotinic receptors and respond directly to nicotine and acetylcholine, producing transient elevations in intracellular calcium. The significance of this opus is that it may provide a mechanism for the taste disturbances that are a side effect of certain anticholinergic drugs.…”
Section: Research In Progressmentioning
confidence: 99%
“…HBO cells were derived from two male and two female volunteers and were developed in Dr. Ozdener's lab at Monell Chemical Senses Center, as a model of human TRCs in vivo. HBO cells stably display all molecular and physiological features characteristic of mature taste cells and exhibit an increase in intracellular calcium ([Ca 2+ ] i ) in response to taste stimuli representing all five taste qualities, indicating the presence of all known signaling pathways [5,[21][22][23][24][25]. HBO cells were cultured as described earlier [5,21,22] and were used between passages 4 and 8.…”
Section: Hbo Cell Culturementioning
confidence: 99%
“…HBO cells stably display all molecular and physiological features characteristic of mature taste cells and exhibit an increase in intracellular calcium ([Ca 2+ ] i ) in response to taste stimuli representing all five taste qualities, indicating the presence of all known signaling pathways [5,[21][22][23][24][25]. HBO cells were cultured as described earlier [5,21,22] and were used between passages 4 and 8. HBO cells express all four ENaC subunits [5,23].…”
Section: Hbo Cell Culturementioning
confidence: 99%
See 1 more Smart Citation
“…A similar mechanism may also be involved in the aversive responses to ethanol at high concentrations [ 92 ]. In support of this mechanism, both in rodent and human taste receptor cells, nAChRs are expressed in TRPM5 positive cells [ 93 , 94 ]. These studies suggest that both TRPM5-dependent and TRPM5-independent but nAChR-dependent pathways are present in bitter taste cells.…”
Section: Potential Role Of Trpa1 and Trpv1 As A Bridge Between Tasmentioning
confidence: 99%